Insecticidal activity of ethanolic plant extracts on Aedes aegypti larvae - Álvarez-Valverde, Victor (2023)
The objective of this study was to determine the larvicidal activity against A. aegypti of ethanolic extracts of plants commonly found in Costa Rica. [Methodology] Larvicidal activity of ethanolic extracts of plants was determined in this study using the WHO/VBC/81.807: WHO/VBC/81. from 1981. An analysis PROBID for dose response was conducted to determine LC50 of the most prominent extracts. [Results] A total of six extracts with the highest toxicity were chosen, with the stem extract of Ipomoea cairica having the lowest LC50 of 0.0341 mg/mL, followed by I. cairica leaf extract with an LC50 of 0.121 mg/mL. The larvicidal activity of ethanolic extracts of plants was determined in this study, with an emphasis on the larvicidal potential of I. cairica as an environmentally friendly alternative for the control of A. aegypti.[Conclusions] The larvicidal activity for ethanolic extracts of different plants, with an emphasis on the larvicidal potential of I. cairica as an environmentally friendly alternative for the control of A. aegypti